Social inequality, environmental justice and water policy In Buenos Aires - Merlinsky, Maria Gabriela (2012)
Privatisation of potable water and sanitation services in the Metropolitan Area of Buenos Aires during the 1990s led to important consequences in terms of investment and equality in the provision of the services. A new period was started in 2006 with the creation of the State-run company Agua y Saneamientos Argentinos SA, which became responsible for managing the provision of water and sewerage services in the region. Today, the company has to deal with the historical backwardness in terms of investment, the growing pressure from the population demanding access to the services, and the significant inequality of the covered area. On the other hand, due to the public impact of the court case regarding the sanitation of Matanza-Riachuelo basin, different territorial collectives have reformulated their demands for infrastructure works by including environmental terms. Besides, the Supreme Court of Justice has required the joint coordination of the works by Agua y Saneamientos Argentinos SA and the Authority of the basin. This means that water and sanitation management must answer to a great variety of actors and be able to operate in highly conflictive areas while meeting, at the same time, the environmental goals. This article describes the main actors involved in water and sanitation management in the Metropolitan Area of Buenos Aires and their approaches to the new plans of expansion of the services. The focus is to identify the opposing interests in terms of the distribution (which territories are the priority for the expansion of the water and sanitation networks); the implementation timetable (how to define the order of the works); and the emergence of different criteria of social and environmental justice. To this effect, we present an in-depth analysis of interviews to public officers, technicians and representatives of social organisations.